ZAKAT UTILIZATION MODEL CANVAS AS A FUNDRAISING STRATEGY FOR AMIL ZAKAT INSTITUTIONS IN SOUTHEAST SULAWESI - Miftahur Rahman Hakim; Istiqomah Shariati Zamani; Rawdatul Amanah; Isya Zulhaja (Academic Bright Collaboration, 2026)
This study aims to analyze the strategies employed by Amil Zakat Institutions (LAZ) in Southeast Sulawesi to enhance zakat collection using the Business Model Canvas integrated with the Social Enterprise Model Canvas approach. A descriptive qualitative method was applied, focusing on two institutions: Baitul Maal Hidayatullah (BMH) and Wahdah Inspirasi Zakat (WIZ). Data were collected through observation, in-depth interviews, and document analysis. The results reveal that strategic collaboration with public institutions, such as Baznas and the Ministry of Religious Affairs, as well as partnerships with private companies like PLN and Telkomsel, significantly improve zakat collection performance. Additionally, diversification of funding channels and the adoption of digital technology expand outreach, enhance transparency, and strengthen accountability in zakat management. This study is limited to two LAZ institutions in Southeast Sulawesi, which may restrict generalizability. However, the findings provide practical insights for zakat institutions in developing collaborative networks and leveraging digital innovation to improve performance. This research offers a novel integration of the Business Model Canvas and Social Enterprise Model Canvas in the context of zakat management, highlighting the importance of cross-sector collaboration and digital transformation to increase efficiency, transparency, and public trust in zakat institutions.